2011
DOI: 10.1186/1423-0127-18-81
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum alters NMDA receptor 1A and 2A/B expression on neonatal hippocampal neurons in rats

Abstract: BackgroundHigh aluminum (Al) content in certain infant formula raises the concern of possible Al toxicity on brain development of neonates during their vulnerable period of growing. Results of in vivo study showed that Al content of brain tissues reached to 74 μM when oral intake up to 1110 μM, 10 times of that in the hi-Al infant formula.MethodsUtilizing a cultured neuron cells in vitro model, we have assessed Al influence on neuronal specific gene expression alteration by immunoblot and immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Some protocols say to dissect the cerebral cortex in cold PBS or HBSS [ 2 , 3 ]. The dissection of the pia mater and blood vessels can take considerable time, and the metabolism of fetal rat neurons is very robust.…”
Section: Methodsmentioning
confidence: 99%
“…Some protocols say to dissect the cerebral cortex in cold PBS or HBSS [ 2 , 3 ]. The dissection of the pia mater and blood vessels can take considerable time, and the metabolism of fetal rat neurons is very robust.…”
Section: Methodsmentioning
confidence: 99%
“…The main route of Al excretion is the urine; therefore, subjects with kidney malfunction or immature kidney, such as nephropathy patients or neonates, might experience toxic accumulation of Al in the body [ 12 ]. Infant formula is the primary food source for bottle-fed neonates.…”
Section: Introductionmentioning
confidence: 99%
“…Infant formula is the primary food source for bottle-fed neonates. The study of Yuan et al reviewed several other studies and reported that most commercial infant formulas contained higher Al (6.5 μM to 87 μM) than human breast milk (0.2 μM to 1.7 μM) [ 12 ]. Infants display rapid growth and their brain-blood-barrier, detoxification system (liver), and excretory system (kidney) are not well-developed [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations